Functional Analysis of Four Terpene Synthases in Rose-Scented Pelargonium Cultivars (Pelargonium × hybridum) and Evolution of Scent in the Pelargonium Genus - Blerot, Bernard; Martinelli, Laure; Prunier, Cécile; Saint-Marcoux, Denis; Legrand, Sylvain; Bony, Aurélie; Sarrabère, Loïc; Gros, Florence; Boyer, Nicolas; Caissard, Jean-Claude; Baudino, Sylvie; Jullien, Frédéric (Frontiers in Plant Science, 2018)
Pelargonium genus contains about 280 species among which at least 30 species are odorant. Aromas produced by scented species are remarkably diverse such as rose, mint, lemon, nutmeg, ginger and many others scents. Amongst odorant species, rose-scented pelargoniums, also named pelargoniums rosat, are the most famous hybrids for their production of essential oil (EO), widely used by perfume and cosmetic industries. Although EO composition has been extensively studied, the underlying biosynthetic pathways and their regulation, most notably of terpenes, are largely unknown. To gain a better understanding of the terpene metabolic pathways in pelargonium rosat, we generated a transcriptome dataset of pelargonium leaf and used a candidate gene approach to functionally characterise four terpene synthases (TPS), including a geraniol synthase, a key enzyme responsible for the biosynthesis of the main rose-scented terpenes. We also report for the first time the characterisation of a novel sesquiterpene synthase catalysing the biosynthesis of 10-epi--eudesmol. We found a strong correlation between expression of the four genes encoding the respective TPSs and accumulation of the corresponding products in several pelargonium cultivars and species. Finally, using publically available RNA-Seq data and de novo transcriptome assemblies, we inferred a maximum likelihood phylogeny from 270 pelargonium TPSs, including the four newly discovered enzymes, providing clues about TPS evolution in the Pelargonium genus. Notably, we show that, by contrast to other TPSs, geraniol synthases from the TPS-g subfamily conserved their molecular function throughout evolution.